An Empirical Stopping Rule for Debugging and Testing Computer Software - Forman, Ernest H.; Singpurwalla, Nozer D. (Journal of the American Statistical Association, 1977)
In this article we introduce the problem of computer software reliability and discuss a probabilistic model for describing the failure of software. We suggest a procedure for estimating the parameters of the model and propose a stopping rule for debugging the software. We apply our procedures to some published data on software failures.